Whole language learning approaches in indonesian primary schools - Muzaki, Ferril Irham (2022)
Along with the flow of information that provides an opportunity for the philosophy community to establish skills and abilities that are the skills to develop the potential and capabilities and skills that are the capabilities and skills in designing data and facts. It is in line with the development of digital currents along with the ability to develop information and communication flows and skills designed to adapt to the ability to solve social problems as well as the skills to elaborate. Adaptation on the development of a meaningful epoch on self-reliance and the ability to adapt to the changing times demanding the ability to establish following with the skills to adapt to various data and facts. Which accompanied the pace of the development of the demands to equality and philosophical skills to the meaning of life which is a positive elaboration of the various works of individuals and society.